Effects of mineralocorticoid receptor gene disruption on the components of the renin-angiotensin system in 8-day-old mice - Hubert, Christine; Berger, Stefan; Schütz, Günther (Molecular endocrinology, 1999)
Targeted disruption of mineralocorticoid receptor (MR) gene results in pseudohypoaldosteronism type I with failure to thrive, severe dehydration, hyperkalemia, hyponatremia, and high plasma levels of renin, angiotensin II, and aldosterone. In this study, mRNA expression of the different components of the renin-angiotensin system (RAS) were evaluated in liver, lung, heart, kidney and adrenal gland to assess their response to a state of extreme sodium depletion. Angiotensinogen, renin, angiotensin-I converting enzyme, and angiotensin II receptor (AT1 and AT2) mRNA expressions were determined by Northern blot and RT-PCR analysis. Furthermore, in situ hybridization and immunohistochemistry allowed us to identify the cell types involved in the variation of the RAS component expression. In the heterozygous mice (MR+/−), compared with wild-type mice (MR+/+), there was no significant variation of any mRNA of the RAS components. In MR knockout mice (MR−/−), compared with wild-type mice, there were significant increases in the expression level of several RAS components. In the liver, angiotensinogen and AT1 receptor mRNA expressions were moderately stimulated. In the kidney, renin mRNA was increased up to 10-fold and in situ hybridization showed a marked recruitment of renin-producing cells; however, the levels of angiotensin-I converting enzyme mRNA and AT1 mRNA were not changed. Interestingly, in adrenal gland, renin expression was also strongly up-regulated in a thickened zona glomerulosa, whereas AT1 mRNA expression remained unchanged. Altogether, these results demonstrate that in the MR knockout mice model, RAS component expressions are differentially altered, renin being the most stimulated component. Angiotensinogen and AT1 in the liver are also increased, but the other elements of the RAS are not affected.
Gesehen am 18.02.2019